A Prospective Study Comparing Diagnosis of Neck Swellings by Fine Needle Aspiration Cytology with Histopathology - Muhammad Wasif Saleem, Shazia Hashmat, Azhar Rashid, Dolat Singh, Shomaila Ameer Alam, Taqia Fauzia (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To to correlate the fine needle aspiration cytology findings with histopathology findings of specimens from neck swellings. Study Design; Cross-Sectional Observational Setting: Pathology Department, Chandka Medical College, Larkana Period: June 2021 to June 2023 Methods: This study consisted of neck swelling samples received in the Department of Pathology by FNAC or excision. Both Cytology and Histopathology were evaluated by an experienced pathologist. Diagnoses of cytology were compared with the histopathological examination and the data was recorded into groups that comprised of lymph nodes, thyroid gland, and salivary glands. Lesions that did not fit into these groups were classified into as “others”. Data was entered and analyzed using SPSS Version-22. Results: There were a total of 261 cases of neck swelling samples received in our department. Most of the cases were due to lymph node (n=104) pathologies notably due to reactive hyperplasia and tuberculosis. The thyroid gland (n=95) was the second most common region for FNAC and most samples showed the diagnosis of colloid goiter followed by follicular adenomas. There were n=30 samples of salivary glands whereas n=32 were classified into others. Overall sensitivity and specificity were variable among the regions of FNAC with the highest being (100%) in the salivary glands and lesions classified into others category. Practical Implication: Comparing neck swelling diagnosis via Fine Needle Aspiration Cytology (FNAC) with Histopathology is vital to validate FNAC’s accuracy before definitive treatment. It ensures informed decision-making, avoiding unnecessary surgeries and minimizing risks. Conclusion: FNAC of the neck swellings is a highly accurate technique and provides the first line of diagnosis. However, FNAC does have its own limitations and this technique should always be complemented by a confirmatory histopathology. Keywords: Fine needle Aspiration Cytology, Neck Swellings, Lymph node, Salivary Glands, Thyroid Glands